Artificial Intelligence in Foreign Language Teaching – Insights from an Interview with ChatGPT and Bard - Thomas Tinnefeld (Journal of Linguistics and Language Teaching)
This article presents a comprehensive interview conducted with ChatGPT and Google Bard, investigating the role of Artificial Intelligence (AI) in the domain of Foreign Language Teaching. The primary objective of this interview, supported by subsequent analysis, is to provide valuable insights into the use, significance, and functions of AI in the context of foreign language teaching. Conducting this interview was motivated by the belief that discussing AI without seeking the opinions and estimations of prominent chatbots would be a notable gap in existing modern research. Both ChatGPT and Bard were posed the same ten questions. These questions explored various aspects, including AI as a paradigm shift in teaching methodology, the most affected areas by AI, the changing roles of teachers and students in the wake of AI, the future importance of language education, the assistance of AI in lesson preparation, the role of AI as a direct learning partner for students, the impact of AI on student assessment, and the future development of foreign language methodology. The responses obtained were, at times, predictable, while in other instances, they proved remarkable and insightful. It is crucial to emphasise that these AI systems should not be solely relied upon as references. It is highly recommended to compare their assessments with those of human experts and other publications to attain a more comprehensive understanding. From the perspective of these two AI systems, this interview represents the current state of the art.